Transformation of single MOF nanocrystals into single nanostructured catalysts within mesoporous supports: a platform for pioneer fluidized-nanoreactor hydrogen carriers - Luz, Ignacio; Soukri, Mustapha; Lail, Marty (Chemical communications (Cambridge, England), 2018)
Well-dispersed nanostructured catalysts along mesoporous materials have been systematically prepared via a novel multistep approach involving either the pyrolysis under nitrogen, the calcination under oxygen or the reduction under hydrogen of MOF nanocrystals decorated with transition metal complexes and previously confined within the mesoporous cavities via novel solid state synthesis. The resulting supported nanostructured catalysts can be composed of metals, metal oxides, heteroatom-doped carbons and combinations thereof depending on the transformation conditions. The pioneering concept of Fluidized-Nanoreactor Hydrogen Carriers has been proposed for the first time by using the resulting nanostructured catalysts within fluidized mesoporous silica.